Phenotypic plasticity in the Antarctic fish Trematomus newnesi (Nototheniidae) from the South Shetland Islands - Piacentino, Gabriela Laura Maria; Barrera Oro, Esteban (Polar Biology)
The presence of the two morphs, “typical” and “large mouth”, in the Antarctic fish species Trematomus newnesi (Perciformes, Notothenioidei) was recorded for the first time in nearshore waters of the South Shetland Islands (Potter Cove) and western Antarctic Peninsula (Petermann Island). The two morphs were distinguishable in specimens of 60–241 mm total length (TL); about 30% of the specimens constituted intermediate forms. In addition to the previously known characters separating the morphs, we found that the “relative size of the eye” can also be used to identify smaller and larger fish of the typical morph. The ecological significance of the two morphs remains unclear. Ratios of diagnostic characters for identifcation of the species at two size ranges (60–131 and 132–241 mm TL) are provided. Fil: Piacentino, Gabriela Laura Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Barrera Oro, Esteban. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina